PENGARUH POLA ASUH ORANG TUA YANG RELIGIUS DAN YANG MENGGUNAKAN GAWAI TERHADAP MORAL AGAMA ANAK DI MI MUHAMMADIYAH RINGIN ANOM WONOSEGORO - Mushoffi, Basyirotul; Wahidin, Wahidin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2022)
Every parent wants their child to have a good, moral, and religious personality. Parents are the first and foremost personal shapers in their children's lives. Parents' personalities, attitudes, and ways of life are elements of education that will indirectly be transmitted to a child's personality. This study uses quantitative research methods with data analysis using multiple linear regression involving 34 samples using purposive sampling technique. There are three data collection instruments that are declared valid by expert and reliable validators. The instruments include the scale of religious parenting, the scale of the use of gadgets, and the moral scale of children's religion. The results showed that 1) The effect of religious parenting variable (X1) on children's religious morals (Y) is known to be sig. for the effect of X1 on Y is 0.0 0.05 and the t value is 5.743 t table is 2.262, then H0 is rejected and H1 is accepted. So it can be concluded that H1 is accepted and there is an effect of X1 on Y. 2) The effect of using gadgets (X2) on children's religious morals (Y) is known to be sig. X2 is 0.464 0.05. And the value of t count 0, 741 2,262, then H0 is accepted and H2 is rejected. It can be concluded that there is no influence between the use of gadgets (X2) on children's religious morals (Y). 3) Furthermore, in the F test, the sig value is known. for the effect of X1 and X2 simultaneously on Y is 0.000 0.05 and the value of f count is 18.811 f table 4.10, so it can be concluded that H3 is accepted which means that there is an effect of X1 and X2 simultaneously on Y.